Outcomes for life sentence prisoners in England and Wales following release from custody. - McSweeney, Tim (International Journal of Population Data Science, 2026)
People serving a life sentence in England and Wales must complete a minimum term in prison, set by the courts, before they can be considered for release by the Parole Board. Those ‘lifers’ recommended for release are subject to monitoring, restrictions, and supervision and serve this sentence for the rest of their lives. They can be returned to custody if they break their licence conditions. This independent research, funded by the Dawes Trust and undertaken in partnership with the Prison Reform Trust, uses de-identified, individual-level administrative records from the Data First Prisoner Custodial Journey Dataset to report on the extent and nature of post-release rates of recall, custodial reconviction, and serious further offending by ‘lifers’ and other prisoners released from custody in England and Wales between 2011 and 2021. These outcomes were assessed at one, two, three, five, and ten-year follow-up periods. It also identifies risk and protective factors associated with these outcomes for life sentence prisoners. These insights will be used to generate public benefits by informing a better understanding of how the implementation, development, and delivery of parole arrangements can shape post-release outcomes for ‘lifers’ and other prisoners.